Rheological characteristics of hydroxyethylcellulose -based gels - Улізко, Ігор Віталійович; Трохимчук, Віктор Васильович; Чуєшов, Владислав Іванович (ScienceRise: Pharmaceutical Science, 2016)
Aim. Study of structural and mechanical properties of gel bases with hydroxyethylcellulose (HEC) for further development of anti-inflammatory action gel. Methods. Pharmaco-technological, physical-chemical and structural-mechanical methods of study have been used. Structural and mechanical properties of the developed gel have been studied using rotational viscometer «Rheolab QC» («Anton Paar», Austria) with coaxial cylinders CC27/S-SN29766. Results. Optimum concentration of hydroxyethylcellulose has been determined as 2 %, that provides the required structural-mechanical properties of gel base. It has been determined that gel base with hydroxyethylcellulose belongs to Newtonian flow type with plastic properties and has thyxotropic properties. The calculated mechanical strength value of the studied gel base is from 1,07 to 1,28 that allows forecasting the drug’s stability in production and storage. The obtained data will be used in development of anti-inflammatory action gel. Conclusion. Optimum composition of gel base with hydroxyethylcellulose for development of anti-inflammatory action gel